Analysis of the quality of root canal preparation and retreatment using different instruments associated or not with different irrigant agitation protocols - Duque, Jussaro Alves (2019)
Introduction: The objectives were: articles I and II - to evaluate the quality of preparation in curved canals of reciprocating systems and cyclic fatigue of new and used instruments; article III - to evaluate the quality of the preparation, in curved canals, of rotary systems and resistance to torsional and cyclic fatigue ,of the new and used glidePath and final instruments, respectively; article IV - to evaluate the quality in the retreatment of curved canals with different systems and the cyclical fatigue, of new and used instruments; article V - evaluate the efficiency in the removal of filling material with different irrigation protocols. Methodology: articles I, II and III - the following instrumentation systems were used: Reciproc Blue 25.08 and 40.06; WaveOne Gold 25.07 and 35.06; ProDesignR 25.06 and 35.05; BT-Race 10.06, 35.00 and 35.04; Sequence Rotary File 15.04, 25.06 and 35.04; ProDesign Logic 25.01, 25.06, and 35.05. Each system was used on 3 teeth. Article I - the transportation, volume and untouched areas were evaluated. Article II - cyclical fatigue of new and used reciprocating instruments were evaluated. Article III - transport, centralization, volume, torsional fatigue and cyclic fatigue of the rotary systems were evaluated. Article IV - the canals were filled and divided according to the retreatment systems: Reciproc 25.08 and 40.06, Reciproc Blue 25.08 and 40.06, Pro-R 25.08 and 40.06 and ProDesign LogicRT 25.08 and 40.05. One instrument was used per tooth. The remaining filling material was measured, the working time required for the instrument 25 to reach working length and cyclic fatigue. Article V - the following irrigation protocols were applied: Continuous Ultrasonic Irrigation with Irrisafe, Continuous Ultrasonic Irrigation with NiTiSonic, Passive Ultrasonic Irrigation with Irrisafe, Passive Ultrasonic Irrigation with NiTiSonic, Eddy and XP-endoFinisherR. The volume of filling material removal was evaluated. Results: I WaveOne Gold presented greater increase in volume and there was no difference in transport and untouched areas. II ProdesignR presented greater resistance to cyclic fatigue. III - there was no difference in transportation, centralization and volume. Torsional fatigue, Sequence Rotary File and ProDesign Logic showed higher values torque and angular deflection, respectively; in cyclic fatigue ProDesign Logic was more resistant. IV ProDesign LogicRT removed more and faster filling material. In cyclic fatigue, Reciproc Blue and ProDesign LogicRT were more resistant. V - There were no differences among the irrigation protocols. Conclusions: I - all the systems presented good quality in the preparation of the root canal. II - ProDesignR presented greater resistance to cyclic fatigue. III - all the systems presented good quality in the preparation, Sequence Rotary File presented higher torque and ProDesign Logic greater angular deflection and cyclic resistance. IV ProDesign LogicRT removed more remaining filling material and was faster. Reciproc Blue and ProDesign LogicRT had greater cyclic resistance. IV - No protocol completely removed the filling material and there was no difference among them.